2008
DOI: 10.1007/s11666-008-9189-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of HVOF-Sprayed WC-(W,Cr)2C-Ni Coatings

Abstract: The composition WC-(W,Cr) 2 C-Ni is one of the standard compositions used for the preparation of thermally sprayed coatings by high velocity oxy-fuel (HVOF) spraying. Surprisingly, this composition has been poorly investigated in the past. Frequent use of commercial designations WC-ÔCrCÕ-Ni, WC-Cr 3 C 2 -Ni, and WC-NiCr indicates the insufficient knowledge about the phase compositions of these powders and coatings. The properties of these coatings differ significantly from those of WC-Co and WC-CoCr coatings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…1. Detailed characterization of their microstructure can be found elsewhere (Ref 31,32,34,35); their basic mechanical properties are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…1. Detailed characterization of their microstructure can be found elsewhere (Ref 31,32,34,35); their basic mechanical properties are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are variations in contents of the components in the range of 1-4 % from different manufacturers [2,3]. The composition contains a lower binder metal content than other WC-based compositions but can be sprayed with a high deposition efficiency [15,16].…”
Section: Wc-20"cr3c2"-7nimentioning
confidence: 99%
“…The metallurgical processes during feedstock powder preparation and spraying for this composition have been studied in detail only recently [11,15,16]. The most specific feature is the formation of (W,Cr)2C.…”
Section: Wc-20"cr3c2"-7nimentioning
confidence: 99%
See 1 more Smart Citation
“…Lutz-Michael Berger et al [12] reported that WC-(W,Cr)2C-Ni coatings are having much superior oxidation and corrosion resistance to that of other commercial WCbased coatings and discussed that the composition WC-(W,Cr)2C-Ni can bridge the gap between WC-Co and Cr3C2-NiCr with regard to oxidation and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%